2002
DOI: 10.3368/lj.21.1.156
|View full text |Cite
|
Sign up to set email alerts
|

No Teens Allowed: The Exclusion of Adolescents from Public Spaces

Abstract: The current practice of excluding adolescents from public landscapes is explored through a review of public policies and common design practices that restrict their use of places. Policies reviewed include curfew and skateboarding ordinances. Design practices related to four types of environments-commercial areas, parks, neighborhoods, and schools-are discussed. The policies define when and where teens cannot get together and design practices often do not provide an alternative. For example, clients' request t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 8 publications
0
22
0
7
Order By: Relevance
“…Même si les centres commerciaux issus du Nouvel urbanisme ont l'apparence d'espaces publics favorables au rassemblement, il n'en demeure pas moins que ce sont des espaces « contrôlés », surveillés par les établissements privés qui s'y trouvent et par la police (Low 2000;Vivoni 2009;Flusty 2001). Même les parcs publics, où l'on pourrait aménager des aires plus intimes sont intentionnellement conçus pour que leurs moindres recoins soient visibles depuis une voiture de patrouille (Kitchen 2005;Mccormick 2006;Owens, 1997Owens, , 2002. Si les adolescents n'ont pas la possibilité de se rassembler ou d'utiliser les lieux publics, c'est qu'ils sont perçus comme des éléments négatifs (Kato, 2009;Owens, 1997Owens, , 2002.…”
Section: « L'adolescent » : Résultat Des Changements Urbainsunclassified
See 2 more Smart Citations
“…Même si les centres commerciaux issus du Nouvel urbanisme ont l'apparence d'espaces publics favorables au rassemblement, il n'en demeure pas moins que ce sont des espaces « contrôlés », surveillés par les établissements privés qui s'y trouvent et par la police (Low 2000;Vivoni 2009;Flusty 2001). Même les parcs publics, où l'on pourrait aménager des aires plus intimes sont intentionnellement conçus pour que leurs moindres recoins soient visibles depuis une voiture de patrouille (Kitchen 2005;Mccormick 2006;Owens, 1997Owens, , 2002. Si les adolescents n'ont pas la possibilité de se rassembler ou d'utiliser les lieux publics, c'est qu'ils sont perçus comme des éléments négatifs (Kato, 2009;Owens, 1997Owens, , 2002.…”
Section: « L'adolescent » : Résultat Des Changements Urbainsunclassified
“…Même les parcs publics, où l'on pourrait aménager des aires plus intimes sont intentionnellement conçus pour que leurs moindres recoins soient visibles depuis une voiture de patrouille (Kitchen 2005;Mccormick 2006;Owens, 1997Owens, , 2002. Si les adolescents n'ont pas la possibilité de se rassembler ou d'utiliser les lieux publics, c'est qu'ils sont perçus comme des éléments négatifs (Kato, 2009;Owens, 1997Owens, , 2002.…”
Section: « L'adolescent » : Résultat Des Changements Urbainsunclassified
See 1 more Smart Citation
“…outcomes (Chaskin and Joseph 2013, Travlou et al 2008, Owens 2002, Shirtcliff 2015. Many of these studies have found that neighborhoods near their home and/or school are in a state of urban decay, with high levels of poverty, racial segregation, and general lack of opportunity.…”
Section: Context Matters: Adolescents Urban Design and The Need Formentioning
confidence: 99%
“…From a youth development perspective, "adolescent-friendly design" to places, such as, downtowns, parks, and schools, can be promoted to accommodate teens rather than discouraging them from idly hanging out [65]. These design decisions should allow for secure social interaction and should be incorporated with the broader community's design initiatives to allow for youth's interaction with other community members and to promote healthy adolescent development [65,66].…”
Section: Policy Implicationsmentioning
confidence: 99%